SUCCOR study. An international european cohort observational study comparing minimally invasive surgery versus open abdominal radical hysterectomy in patients with stage IB1 (FIGO 2009, <4 cm) cervical cancer operated in 2013–2014. (1st November 2019) - Chiva, L; Zanagnolo, V; Kucukmetin, A; Chakalova, G; Raspagliesi, F; Narducci, F; Toptas, T; Meydanli, M; Fagotti, A; Cibula, D; Wydra, D; Póka, R; et al.
Abstract : Introduction/Background: Minimally invasive surgery (MIS) was adopted as an alternative to laparotomy for radical hysterectomy in patients with early-stage cervical cancer before obtaining solid evidence regarding its effect on survival. We studied what was the outcome of patients that underwent Radical hysterectomy for stage IB1 cervical cancer, depending on the different approaches. Methodology: We performed a cohort study involving women who underwent radical hysterectomy for stage IB1 cervical cancer during the 2013–2014 period in 89 centers belonging to 23 European countries. The study included patients with a histologic subtype of squamous-cell carcinoma, adenocarcinoma, or adenosquamous carcinoma. Either preoperative pelvic MRI or vaginal ultrasound indicating tumor diameter <4 cm and no parametrial invasion was mandatory. The primary outcome was the rate of disease-free survival at 4.5 years between MIS vs. open surgery. Patients with history of previous conization were also analyzed separately. A propensity matching score was applied to balance all the relevant variables that were found significant to modify the rate of relapse. Inverse probability weighting-adjusted disease-free survival evaluated the impact of the use of uterine manipulator in MIS. Results: 624 patients were registered of whom 582 fulfilled all the inclusion criteria. With a median follow up of 58 months, patients that underwent open surgery showed a DFS at 4, 5y of 93% vs. 82% in the group of MIS (p=0, 023, HR 3.48; 95% CI: 1.17–9.48). The use of manipulator was associated with a worse DFS in the MIS group (HR 2.38; 95% CI: 1.32–4.29). Overall survival at 4.5y was significantly lower (96% vs.88%) in the group of MIS (p=0, 016). Patients with previous conization did not show differences between both approaches. Conclusion: The risk of relapse and death in the group of MIS was significantly higher. The use of manipulator worsened the outcome among MIS patients. Disclosure: Nothing to disclose.